Communication course for future engineers – effective data presentation and its interpretation during LSP courses - Matuszak, Katarzyna; Szczuka-Dorna, Liliana (Language learning in higher education (Berlin, Germany), 2023)
This activity report describes a sample unit (Effective Data Presentation) from a communication course prepared as part of an Intellectual Output within the BADGE Project, which was carried out by 12 partner universities from 10 countries during 3 academic years (2019–2022). The article first describes the results of a survey which show that language and communication classes need to integrate more LSP competences so that students become better acquainted with both general and specific language. Moreover, the report analyses and explains the existing practical difficulties for language and subject teachers alike in maintaining a distinction between “knowledge of a subject” and “knowledge of the language of a subject.” Secondly, the report presents a sample from a communication course prepared for engineers encompassing effective data presentation and its interpretation during LSP courses. Finally, the article reflects on the future challenges for LSP teachers and the reasons why academics should integrate professional knowledge and specialist language within the same course.